DEVELOPING STUDENT’S VOCABULARY ACQUISITION THROUGH MNEMONIC LOCI METHOD - Marjun, Agustinus; Yuliana, Yohanes Gatot Sutapa; Sudarsono, Sudarsono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study was to examine the use of mnemonic loci method in developing student’s vocabulary acquisition. This classroom action research design conducted to the 27 students of second grade SMP Negeri 3 Ketungau Hulu in academic year 2018/2019. Two cycles of classroom action research were conducted to help the researcher achieve the objective. The data were collected and analyzed in qualitative and quantitative form. The findings showed that there were positive improvements on students’ vocabulary acquisition. This result was exactly supported by the process in teaching and learning, which indicated that students’ interest in learning vocabulary increased. The use of mnemonic loci method combined with picture was useful in assisting students to memorize vocabulary target in the learning process. In conclusion, the researcher was highly recommended that mnemonic loci method combined with picture as aids may be applied in teaching vocabulary. The use of mnemonic loci method was not simply improving students’ vocabulary acquisition but valuable to encourage students in learning vocabulary. Keywords: Classroom Action Research, Mnemonic Loci Method, Teaching Vocabulary